Urine markers for detection and surveillance of bladder cancer - Xylinas, Evanguelos; Kluth, Luis A.; Rieken, Malte; Karakiewicz, Pierre I.; Lotan, Yair; Shariat, Shahrokh F. (Urologic oncology, 2014)
Bladder cancer detection and surveillance includes cystoscopy and cytology. Urinary cytology is limited by its low sensitivity for low-grade tumors. Urine markers have been extensively studied to help improve the diagnosis of bladder cancer with the goal of complementing or even replacing cystoscopy. However, to date, no marker has reached widespread use owing to insufficient evidence for clinical benefit. Pubmed/Medline search was conducted to identify original articles, review articles, and editorials regarding urine-based biomarkers for screening, early detection, and surveillance of urothelial carcinoma of the bladder. Searches were limited to the English language, with a time frame of 2000 to 2013. Keywords included urothelial carcinoma, bladder cancer, transitional cell carcinoma, biomarker, marker, urine, diagnosis, recurrence, and progression. Although several urinary markers have shown higher sensitivity compared with cytology, it remains insufficient to replace cystoscopy. Moreover, most markers suffer from lower specificity than cytology. In this review, we aimed to summarize the current knowledge on commercially available and promising investigational urine markers for the detection and surveillance of bladder cancer. Well-designed protocols and prospective, controlled trials are needed to provide the basis to determine whether integration of biomarkers into clinical decision making will be of value for bladder cancer detection and screening in the future.